PEMANFAATAN SENSOR GYRO PADA SISTEM PENSTABIL KAMERA (GIMBAL) UNTUK PENGAMBILAN GAMBAR VIDEOFRAFI - Ernes, Risa Nadia; Defnizal, Defnizal; Wirawan, Nanda Tommy (Ensiklopedia of Journal, 2024)
The design of the camera stabilizer system (gimbal) aims to reduce vibrations and movements that interfere with the camera when shooting both photos and videos. In the world of videography, a gimbal is a device that a videographer must have, because if a videographer does not have a camera stabilizer (gimbal), there will be concerns that the video capture will not be good. With this gimbal system, it will really help videographers in taking pictures or videos, so that it can support the performance of videographers.Keywords: Arduino, Camera, Gyro, Gimbal, Servo